Using “Enzan No Metsuke” (Gazing at the Far Mountain) as a Visual Search Strategy in Kendo - Kato, Takaaki (Frontiers in Sports and Active Living, 2020)
In Kendo (Japanese fencing), “Enzan no Metsuke” is an important Waza (technique) that is applied by expert Kendo fighters. It involves looking at the opponent's eyes with “a gaze toward the far mountain,” taking in not only the opponent's face but also his or her whole body. Over the last few decades, a considerable number of studies on visual search behaviors in sport have been conducted. Yet, there are few articles that examine visual search behaviors in combat sports, such as martial arts. This study aimed to analyze the visual search strategies used by expert Kendo fighters through sparring practices to discuss what “Enzan no Metsuke” is under experimental, but natural (in situ), conditions. Ten experts, 10 novices, and one Shihan (a master of Kendo) participated in this study. The fighters wore a mobile eye tracker and faced a real opponent. They were instructed to do the following in five different sessions: prepare themselves, practice their offense and defense techniques, and fight in a real Shiai (match). The results indicated differences in the visual search strategies between the Shihan, experts, and novices. The Shihan and experts fixated on their opponent's eyes or head region most of the time and adopted a visual search strategy involving fewer fixations of longer duration. Conversely, novices set their eyes mainly on the opponent's Shinai (sword). Only the Shihan always looked at the opponent's eyes, even during the preparation, offense, and defense sessions. Shihan and experts set their “visual pivot” on the opponent's eyes quietly, even when the opponent tried to attack with the Shinai. Novices, however, moved their eyes up and down based on the influence of their opponent's movements. As these results indicate, novices tried to search for detailed information about their opponent and processed visual information depending on their focal vision, whereas Shihan and experts absorbed information not from their opponent's eyes but from their entire body by utilizing their peripheral vision; this means that Shihan and experts could see an opening or opportunity and react instantaneously by using “Enzan no Metsuke.”